Persistent Inequalities - Haddow, Rodney (Labour / Le Travail, 1995)
The article reviews the book, "Persistent Inequalities," by Howard Botwinick.
Keywords: BOOKS – Reviews; BOTWINICK; Howard; Nonfiction; PERSISTENT Inequalities (Book); WAGE differentials